Partitioning genetic effects due to embryo, cytoplasm and maternal parent for oil content in oilseed rape (Brassica napus L.) - Jian-Guo Wu; Chun-Hai Shi; Hai-Zhen Zhang (Genetics and Molecular Biology, 2006)
Analysis of genetic main effects and genotype x environment (GE) interaction effects on the oil content of oilseed rape (Brassica napus L.) was conducted by using a genetic model for the quantitative traits of seeds in diploid plants. The experiments were carried out over two years with 8 parents and a diallel mating design, which produced F1 and F2 generations. We found that the oil content of rape was simultaneously controlled by embryo genetic effect, cytoplasmic effects and maternal genetic effect as well as GE interaction effects, with the cytoplasmic and maternal effects playing the main role. The results indicate that selection of maternal plants for high oil content would be more efficient than selection based on single seeds. Since the GE interaction effects accounted for 73.69% of the total genetic effects and were more important than the genetic main effects it seems that selection might be influenced by environmental conditions. The estimate of narrow-sense heritability for oil content was 73.52% with the interaction heritability being larger than the general heritability, indicating that the early generations can be used for selection for high oil content. The prediction of genetic effects suggested that the parent cultivars Youcai 601 and Gaoyou 605 were better than the other cultivars for increasing oil content during the breeding of B. napus. The implications for the quantitative trait loci mapping of seed traits interfered by these three genetic systems is also discussed.